Diversity and similarity in parasitic infracommunities of Mylossoma aureum and Mylossoma duriventre (Characiformes, Serrasalmidae) from the Middle Madeira River Basin, Southern Amazonas, Brazil - Pelegrini, Larissa Sbeghen [UNESP]; Ramos, Keythiane Freire; da Silva, Reinaldo José [UNESP]; Dos Anjos, Marcelo Rodrigues (Boletim do Instituto de Pesca, 2024)
A total of 30 specimens of Mylossoma aureum and 30 of Mylossoma duriventre from the Middle Madeira River Basin were examined between October 2020 to March 2021. Eight species of parasites were identified. About 65% of the hosts were parasitized. A total of 386 parasites was collected in M. aureum and 436 in M. duriventre. Species accumulation curves in M. aureum did not reach the asymptote, while in M. duriventre the curves showed tendency to stabilization. Contracaecum sp. larvae was the only endoparasite found. Anacanthorus paraspathulatus was the dominant species in M. aureum. In M. duriventre, the core species with highest parasite indexes was Mymarothecium sp. 3. Margalef’s and Shannon’s diversity indexes were higher in M. aureum. Most of the parasites showed an aggregated distribution pattern. Mymarothecium sp. 1, Mymarothecium sp. 2 and the parasite richness showed a significant positive correlation between its abundance and host length and between Mymarothecium sp. 1 abundance and host weight in M. aureum. All parasites are the first records for the Southern Amazonas. Except A. paraspathulatus, all M. aureum parasites are mentioned for the first time in this host. The three morphotypes of Mymarothecium spp. are probably new species that are in the process of taxonomic description.
Diversidade e similaridade em infracomunidades parasitárias de Mylossoma aureum e Mylossoma duriventre (Characiformes, Serrasalmidae) da Bacia do Médio Rio Madeira, sul do Amazonas, Brasil
Keywords: Amazon fish parasites; Amazonia; Freshwater fish; Pacu; Parasite diversity; Small-scale fisheries